Language and space - Bloom, Paul (Cambridge, Mass. ; London : MIT, 1996)
* The architecture of the linguistic-spatial interface / Ray Jackendoff
* How much space gets into language? / Manfred Bierwisch
* Perspective taking and ellipsis in spatial description / Willem J. M. Levelt
* Frames of reference and Molyneux's question: Crosslinguistic evidence / Stephen C. Levinson
* The confluence of space and language in signed languages / Karen Emmorey
* Fictive motion in language and "ception" / Leonard Talmy
* The spatial prepositions in English, vector grammar, and the cognitive map theory / John O'Keefe
* Multiple geometric representations of objects in languages and language learners / Barbara Landau
* Preverbal representation and language / Jean M. Mandler
* Learning how to structure space for language: A crosslinguistic perspective / Melissa Bowerman
* Space to think / Philip N. Johnson-Laird
* Spatial perspective in descriptions / Barbara Tversky
* A computational analysis of the apprehension of spatial relations / Gordon D. Logan and Daniel D. Sadler
* The language-to-object perception interface: Evidence from neuropsychology / Tim Shallice
* Space and language / Mary A. Peterson, Lynn Nadel, Paul Bloom and Merrill F. Garrett
Bibliografija iza svakog poglavlja
Kazala
Keywords: jezik; prostorna percepcija; lingvistika; neuroznanost; znakovni jezik; psiholingvistika